Tensions within the British Conservative Party in the Context of Brexit - R. I. Blagoveshchenskii (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The paper focuses on tensions within the ruling Conservative and Unionist Party of the United Kingdom of Great Britain and Northern Ireland over its membership in the European Union, which acquired a whole new dimension in the context of Brexit. The case of the Conservative Party is of special interest in this regard not only because it has been the ruling party since 2010 and determines the main directions of the domestic and foreign policies of the state, but also because it is considered to be the most Eurosceptic of all traditional European political parties. However, even the quick overview of the official party documents from 2010–2016 referring to the relations with the EU, clearly shows that Tory lacked unity on that matter. Alongside with the Eurosceptics, who advocated a substantive revision of the EU-UK relations, up to their complete severance, there was a strong faction of the so-called integrationists, who emphasized economic benefits from the continuation of membership in the EU. This split has only worsened after the Brexit referendum and the start of negotiations on the UK’s withdrawal from the EU. The ensuing debates have revealed four factions within the Conservative Party. The first faction includes politicians who strongly support Brexit even without a new deal with the EU. The second faction supports Brexit but insists on a new and better deal with the EU. The third group fully supports T. May’s policy. And, finally, the fourth faction opposes the very idea of Brexit and backs for the second Brexit referendum. This split within the ranks of the Conservative Party, compounded by further polarization of electorate and the rise of non-system parties, poses new challenges for the Tory leaders and their decisions will influence not only domestic and foreign policies of the state, but, to a large extent, the development of international relations in Europe in general.